Identification and classification of 16 new kinesin superfamily (KIF) proteins in mouse genome - Nakagawa, Terunaga (The National Academy of Sciences of the USA, 1997)
KIF (kinesin superfamily) proteins are microtubule-dependent molecular motors that play important roles in intracellular transport and cell division. The extent to which KIFs are involved in various transporting phenomena, as well as their regulation mechanism, are unknown. The identification of 16 new KIFs in this report doubles the existing number of KIFs known in the mouse. Conserved nucleotide sequences in the motor domain were amplified by PCR using cDNAs of mouse nervous tissue, kidney, and small intestine as templates. The new KIFs were studied with respect to their expression patterns in different tissues, chromosomal location, and molecular evolution. Our results suggest that (i) there is no apparent tendency among related subclasses of KIFs of cosegregation in chromosomal mapping, and (ii) according to their tissue distribution patterns, KIFs can be divided into two classes–i.e., ubiquitous and specific tissue-dominant. Further characterization of KIFs may elucidate unknown fundamental phenomena underlying intracellular transport. Finally, we propose a straightforward nomenclature system for the members of the mouse kinesin superfamily.